Faktor-faktor yang mempengaruhi Kunjungan Nifas di Puskesmas Jepon Kabupaten Blora Tahun 2012 - Ummi Trisnawati; Bahiyatun Bahiyatun; Sri Wahyuni (S) (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2013)
In 2010 the number of maternal death after delivery in Indonesia was 41%. The coverage postpartum visit in puskesmas jepon in 2011 was 72,53%. Regar-ding to improve the coverage postpartum visit, there were several things have done such as establishing maternity class and distributing KIA booklet for free. Type of this reaseach is the correlation approach of cross sectional. The sample took from all postpartum mothers from the total population based on its criteria, 49 respondent. Univariat and bivariat with chi-square has been the based of the data analysis. UnIvariat analysis shows that the education of the respondent of elementary and secondary school is 57,1% the positive maternal attitude against postpartum visit is 55,1% , good spousal support 59,2% and complete post partum visit 59,2%. Bavariat analysis result of the relationship between the education of post partum mother and postpartum visit was x² 0,002 sig = 0,967, found no relationship between education of postpartum mother and postpartum visit. The relationship between postpartum mother and spousal support was x² 5,324 sig = 0,021, means that found the relationship between spousal support and postpartum visit.